Characteristic Exploration of Family Fabaceae Leaf Trichomes - Roimil Latifa; Endrik Nurrohman; Samsun Hadi (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to explore the characteristics of trichomes from the Fabaceae family. This type of research is exploratory descriptive research. Direct exploration and laboratory observation methods were used in the research. This research was carried out from March 2022 to January 2023. This research was carried out at the UMM Malabar City Forest and Biology Laboratory. Observation of trichomes using SEM. The research data obtained were analyzed using descriptive statistics. The results of the research show that there are variations in the characteristics of Fabacea family trichomes in the Malabar forest of Malang City. There are two varieties of trichomes, there are three forms of trichomes, namely subulate, osteolate and globular, the highest average number is Bauhinia purpurea leaf trichomes and the fewest are Albizia chinensis and Senna siamea, the trichomes with the longest size are Delonix regia and the shortest are Erythrina trichomes variegata, the narrowest trichomes are A. chinensis and the widest are E. Variegata. The results of the research can be used by stakeholders to become a consideration for selecting plant species in city parks by using plants that can help improve air quality in addition to considering aesthetics.